Economic and environmental impacts of China's imported iron ore transport chain under road-to-rail policy: an empirical analysis based on the Bohai Economic Rim. Issue 6 (1st November 2020) - Zhao, Yuzhe; Zhou, Jingmiao; Fan, Yujun; Feng, Mingming; Zhang, Zijian
Abstract: The imported iron ore transport chain is a complex system concerning different transport modes, means, and routes within water areas and various regions on the land. However, the relevant literature has only tackled the carbon mitigation of a single transport mode in a specific region. Under China's road-to-rail policy, this article investigates the total transport cost, carbon and nitrogen emissions of the imported iron ore transport chain between Brazil and the steel enterprises in the Bohai Economic Rim (BER), and established a model to select the optimal transport plan. Inspired by the policies calling for capacity structure reform of steel industry and energy structure adjustment of highway transport, the authors set up 12 scenarios and estimate the cost and emissions. The results demonstrate the positive economic and environmental impacts of the road-to-rail policy, the development of multimodal transport of railway and waterway (MTRW), and the capacity structure adjustment of the steel industry. However, the impacts of capacity structure adjustment might be marginalized. Besides, natural gas trucks are proved important to fulfilling the goal of clean highway transport. Finally, the discussion on the recent policy of liquidation mechanism reform reveals that the unit railway transport cost should be reduced moderately. Otherwise, the reduction cannot save total transport cost, but cause greater carbon and nitrogen emissions.